Evaluation of Accuracy of a Theoretical Model for Predicting the Necrosed Tissue Volume during Focused Ultrasound Surgery - Hynynen, Kullervo; Fan, Xiaobing; Damianou, Christakis A. (My University, 1995)
The concept of thermal dose as a predictor for the size of the necrosed tissue volume during high-intensity focussed ultrasound surgery was tested. The sensitivity of the predicted lesion size to the uncertainties in the iso-dose constant, attenuation coefficient, and thermal dose threshold of necrosis was studied. The predicted lesion size appears to be independent of attenuation at some high attenuation values and certain depth in tissue. Thus, for a given target depth, a proper selection of frequency could minimize the lesion size variability due to uncertainty in the tissue attenuation. The predicted lesion size was less dependent on the uncertainties in the iso-dose constant and thermal dose of necrosis. The predictions of the model were compared with experimental data in rabbit muscle, and experimental data in cat and rat brain measured by others. The agreement was found to be good in most of the experiments. Similarly, the model was found to predict well the trends of increasing power and pulse duration. 0885-3010/95$04.00 © 1995 IEEE
Keywords: Necrosed tissue volume; Sommerfield integral techniques; Ultrasound surgery